International Management The Process of Internationalization and Market Entry Strategies - Fuchs, Manfred (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Gabler, 2022)
This textbook for students and practitioners offers answers to the most important questions and challenges of international management. The main topics are presented and discussed on three levels: (a) the macroeconomic and institutional environment of the global economy, (b) the international firms embedded as players in this environment, and (c) the actual management decisions. The focus is placed both on the characteristics of the individual subject areas (macro-, meso- and microperspective) and on the interdependent connections between these areas. The main interest of this book lies in an application-oriented analysis of the central strategic management decisions in internationalizing companies. This textbook has been recommended and developed for university courses in Germany, Austria and Switzerland. Contents Market entry strategies Theories in international management (concepts and applications) Managerial decision-making and entry strategies (theory vs. reality) Core structure of the global economy and the internationalizing firm The role of evolutionary theory and decision-making in the process of internationalizing firms The author Prof. Dr. Manfred Fuchs is Adjunct Professor of International Management and heads the International Management specialization of the Business Administration master's degree program at the University of Graz. From 1989 to 1995 he was a research assistant at the Starnberger Institut e.V.; 1997/1998 visiting professor at the College d'Europe in Bruges. Manfred Fuchs has been working at the University of Graz since 1995 and conducted extensive field research in the Philippines, China, Colombia, Thailand and Malaysia.
The global economy as the macro-environment -- Theories of internationalization -- Market entry decisions -- Market entry modes -- The coordination and configuration of global value chains (GVCs) -- The management of the multinational firm.
Keywords: International business enterprises; Management; International Business; Management